Mengungkap Sistem Pemberian Kredit Berbasis Religius Magis pada Koperasi Simpan Pinjam Urip Sejahtera Desa Kubutambahan - Ni Komang Evi Sugiani; I Made Pradana Adiputra (Jurnal Ilmiah Akuntansi dan Humanika, 2022)
This study aims to find out how the implementation of a religious-based credit distribution system in the Urip Sejahtera savings and loan cooperative in Kubutambahan Village. This research uses a qualitative research approach. Collecting data in this study using the interview method, the data used are primary and secondary data in which the object of research is the savings and loan cooperative Urip Sejahtera Kubutambahan village. Data analysis uses data reduction, qualitative data presentation. The results of the study showed that the Urip Sejahtera savings and loan cooperative implemented a religious-based credit system with the credit application process added with religious ritual procedures before lending. The implications of this magical religious system are in accordance with Edrawd III's theory of policy implementation, namely communication, resources, disposition, and organizational/bureaucratic structure. This study reveals that the creative steps of KSP Urip Sejahtera with the Religious Credit System were implemented well because it applied a combination of Edward III's policy theory with the master religious system.